Participation in SOS Outreach: a positive youth development program - Keigley, Meghan Ann, author; Coatsworth, J. Douglas, advisor; Riggs, Nathaniel, committee member; Eakman, Aaron, committee member (Colorado State University. Libraries, 2015)
Adolescence can be a time burdened by physical, emotional and social developmental challenges. However, many extracurricular programs now focus on fostering Positive Youth Development (PYD) with a primary goal of helping youth develop positive life skills and positive trajectories. Many of these programs emphasize providing youth with opportunities to develop positive self-identities and life skills that they can apply to other areas of their lives. Studies have demonstrated positive outcomes of these programs, but have also shown that youth participation is key for gaining these benefits. Many youth drop out of these programs before they are able to fully realize the benefits. The purpose of this study was to examine whether various personal, logistic, and experiential factors predict to continued participation in a Colorado-based PYD program. Eighty-eight adolescent, ages 9 - 17 completed surveys following participation in a winter-long program that incorporates positive youth development into snowsport activities. Youth reported on barriers to participation, developmental experiences, self-defining activities, and parental encouragement to participate in the program. Results indicated that demands of the program and parental encouragement for identity exploration were significantly related to participant retention. Additionally, negative developmental experiences, but not positive developmental experiences within the program were significant predictors of participant retention while program specific self-defining activities were not. Finally, self-defining activities did not moderate the relationship between logistical issues and participant retention.